Energy Efficient Modified AODV for Wireless Sensor Network - Katkar, Pallavi S; Ghorpade, Vijay R (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor network are gathering of number of mobile nodes which are associated wirelessly with each other to carry out some tasks. Wireless sensor network are self-configured, infrastructure less network. In a WSN an effective utilization of resources is a vital issue because nodes in the network depend on limited resources like battery power. Hence, energy efficient routing for this network is essential which will provide better performance with the restricted resources. The purpose of this paper is to design energy aware routing protocol; here we consider classical AODV and Modified AODV (M-AODV). This protocol based on remaining energy of each node which will help to lengthen the life of network. Network Simulator NS-3.20 determined for simulation between AODV and M-AODV.